2019
DOI: 10.3389/fvets.2019.00100
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Multi-Center Analysis of Canine Socket Prostheses for Partial Limbs

Abstract: Introduction: Socket prostheses for treatment of distal limb pathology are becoming increasingly prevalent in veterinary medicine, however, limited objective data is available. Objectives of the present study were to retrospectively evaluate owner satisfaction, clinical outcomes, and prognostic factors associated with dogs receiving socket prostheses for partial limbs in a larger patient population. Materials and Methods: Client databases of a single prosthesis provider were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Another investigation indicated that 87.5% of patients (21/24) had the same to improved quality of life as they did prior to receipt of a prosthesis [16]. A third work reported that 89.3% of owners (42/47) said to have accepted to full function following prosthesis placement [78]. Although owner survey-based instruments can be used to evaluate owner perceptions of a canine quality of life and owner expectations regarding canine mobility, The change in the ability to jump up and down compared to before fitting of the stump socket prosthesis (n=12) [79].…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another investigation indicated that 87.5% of patients (21/24) had the same to improved quality of life as they did prior to receipt of a prosthesis [16]. A third work reported that 89.3% of owners (42/47) said to have accepted to full function following prosthesis placement [78]. Although owner survey-based instruments can be used to evaluate owner perceptions of a canine quality of life and owner expectations regarding canine mobility, The change in the ability to jump up and down compared to before fitting of the stump socket prosthesis (n=12) [79].…”
Section: Future Directionsmentioning
confidence: 99%
“…An acceptable function defined as restoration to, or maintenance of, intended activities and performance from pre-injury or pre-disease status that is limited in level or duration (12-22 points). The unacceptable function was defined as all other outcomes (≤ 11 points) with a possible score range of−13-34 [78]. no investigation has been conducted on overall owner satisfaction with prostheses as a treatment option [78].…”
Section: Future Directionsmentioning
confidence: 99%
“…For contraindicated cases of full-limb amputation or when owners are reluctant for such a procedure to be carried out, a distal partial limb amputation could be considered for replacing that injured portion with a prosthetic device (Fitzpatrick et al, 2011;Séguin and Weigel, 2012;Farrell et al, 2014;Mich, 2014;Phillips et al, 2017;Golachowski et al, 2019;Wendland et al, 2019). Prosthetic devices could be a socket prosthesis or exoendoprosthesis (Mich, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Prosthetic devices could be a socket prosthesis or exoendoprosthesis (Mich, 2014). Recently, more socket prosthesis studies have appeared with variable results about owner's satisfaction and complications related to these devices (Phillips et al, 2017;Wendland et al, 2019). Some ruminant patients have also been reported (Desrochers et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation